Changes to Prenatal Care Visit Frequency and Telehealth: A Systematic Review of Qualitative Evidence. Issue 2 (4th February 2023) - Konnyu, Kristin J.; Danilack, Valery A.; Adam, Gaelen P.; Friedman Peahl, Alex; Cao, Wangnan; Balk, Ethan M.
Abstract : Qualitative evidence suggests that health care professionals and patients saw potential benefits but also had some concerns with reduced visit schedules and use of televisits for routine prenatal care. Abstract : OBJECTIVE: To systematically review patient, partner or family, and clinician perspectives, preferences, and experiences related to prenatal care visit schedules and televisits for routine prenatal care. DATA SOURCES: PubMed, the Cochrane databases, EMBASE, CINAHL, ClinicalTrials.gov, PsycINFO, and SocINDEX from inception through February 12, 2022. METHODS OF STUDY SELECTION: This review of qualitative research is a subset of a larger review on both the qualitative experiences and quantitative benefits and harms of reduced prenatal care visit schedules and televisits for routine prenatal care that was produced by the Brown Evidence-based Practice Center for the Agency for Healthcare Research and Quality. For the qualitative review, we included qualitative research studies that examined perspectives, preferences, and experiences about the number of scheduled visits and about televisits for routine prenatal care. TABULATION, INTEGRATION, AND RESULTS: We synthesized barriers and facilitators to the implementation of reduced care visits or of televisits into 1 of 14 domains defined by the Theoretical Domains Framework (TDF) and a Best Fit Framework approach. We summarized themes within TDF domains. We assessed our confidence in the summary statements using the GRADE-CERQual (Grading of Recommendations Assessment, Development and Evaluation—Confidence in Evidence from Reviews of Qualitative research) tool. Four studies addressed the number of scheduled routine prenatal visits, and five studies addressed televisits. Across studies, health care professionals believed fewer routine visits may be more convenient for patients and may increase clinic capacity to provide additional care for patients with high-risk pregnancies. However, both patients and clinicians had concerns about potential lesser care with fewer visits, including concerns about quality of care and challenges with implementing new delivery-of-care models. CONCLUSION: Although health care professionals and patients had some concerns about reduced visit schedules and use of televisits, several potential benefits were also noted. Our synthesis of qualitative evidence provides helpful insights into the perspectives, preferences, and experiences of important stakeholders with respect to implementing changes to prenatal care delivery that may complement findings of traditional quantitative evidence syntheses. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42021272287.